Pengaruh Gaya Kepemimpinan Transformasional, Work-life Balance, dan Kepuasan Kerja terhadap Turnover Intention - Eliana, Fina; Negoro, Dimas Angga (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to explore the role of the influence of transformational leadership styles, work-life balance, and job satisfaction towards turnover intention to employees of PT. Kazeto Putra Perkasa. This research is a causal research with a quantitative method approach and using analysis (PLS-SEM). The respondents of this research are employees of PT. Kazeto Putra Perkasa with a total of 91 respondents and the survey is conducted online via Google Form. The results of this study indicate that the transformational leadership style has a positive effect on job satisfaction, work-life balance has a positive effect on job satisfaction, transformational leadership style has no effect on turnover intention, work-life balance negative effect on turnover intention, job satisfaction has a negative effect on turnover intention. Furthermore, job satisfaction mediates the relationship between transformational leadership style and turnover intention, and job satisfaction mediated the relationship between work-life balance to turnover intention. These findings broaden the knowledge of corporate management with respect to turnover intention to employees of PT. Kazeto Putra Perkasa, work-life balance must be considered in order to increase job satisfaction which can decrease turnover intention. Keywords: Job Satisfaction, Transformational Leadership Style, Turnover Intention, and Work-life Balance